Can Capital Income Taxes Survive? And Should They? - Peter Birch Sørensen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2006)
The paper surveys some main results in the theory of capital income taxation in the open economy; reviews recent trends in international taxation, and discusses alternative blueprints for fundamental capital income tax reform from the perspective of an open economy faced with growing mobility of capital income tax bases.
Keywords: 330; Kapitalertragsteuer; Steuerwettbewerb; Steuerreform; Unternehmensbesteuerung